Analisis Gaya Komunikasi Berbahasa Asertif Pada Program “Desak Anies”. - Hutauruk, Desi Ramadali; April Yanti; Aisyah Arfani Rambe (ELP (Journal of English Language Pedagogy), 2025)
This research examines the language style used by Anies Baswedan in the “Desak Anies” program on Kompas TV, focusing on how assertive communication strategies are adapted to modern media platforms in Indonesia's political landscape. Using a qualitative approach with content analysis, episodes aired between January and December 2023 were analyzed based on McNair’s political communication theory and Austin’s speech act theory. The findings highlight four main assertive communication styles: basic assertion for clarity, empathic assertion for emotional connection, escalating assertion for firm responses, and confrontative assertion for addressing misinformation. By maintaining message consistency across platforms, this study emphasizes how political figures can effectively engage audiences, build trust, and shape public opinion in the digital era. This research contributes to the understanding of political communication strategies in Indonesia's ever-evolving media context.